2009
DOI: 10.1002/pd.2326
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulfatase deficiency and contiguous gene deletion syndrome amongst pregnant patients with low serum unconjugated estriols

Abstract: ObjectiveTo ascertain all prenatally diagnosed cases of Steroid Sulfatase (STS) deficiency in British Columbia between August 2002 and July 2007 to determine the incidence of this condition, the clinical and laboratory findings, and the risk of a contiguous gene deletion syndrome.MethodsWe reviewed the medical records of these patients to obtain detailed information about the maternal serum screening results, family history, investigations performed, and outcome of the pregnancy.ResultsThirty pregnant patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Two recent reports provide findings for CGDS prevalence in unbiased series of STSD cases identified during prenatal screening; discrepancies in data between these studies may reflect differences in their follow-up protocols. As noted above, Kent et al (2008) documented CGDS in 3 of 16 STSD index cases (18.7%, 95% CI 4-46), while Langlois et al (2008), found 1 CGDS case among 29 consecutive STSD cases. Combining these data using a random effects model yields an overall estimate of 9.8% (95% CI 1.7-39, test for heterogeneity = 0.2, I 2 = 58%).…”
Section: Discussionmentioning
confidence: 61%
“…Two recent reports provide findings for CGDS prevalence in unbiased series of STSD cases identified during prenatal screening; discrepancies in data between these studies may reflect differences in their follow-up protocols. As noted above, Kent et al (2008) documented CGDS in 3 of 16 STSD index cases (18.7%, 95% CI 4-46), while Langlois et al (2008), found 1 CGDS case among 29 consecutive STSD cases. Combining these data using a random effects model yields an overall estimate of 9.8% (95% CI 1.7-39, test for heterogeneity = 0.2, I 2 = 58%).…”
Section: Discussionmentioning
confidence: 61%
“…None of our patients had any clinical findings suggestive of a contiguity syndrome [i.e. cognitive impairment, short stature, recessive form of chondrodysplasia punctata, Kallman syndrome (anosmia and hypogonadotropic hypogonadism)], which have been reported in up to 8% of patients diagnosed prenatally as STS deficient . However, one patient was diagnosed with Tourette syndrome and another (previously reported in the literature) had RDEB.…”
Section: Discussionmentioning
confidence: 62%
“…Excessive accumulation of cholesterol sulfate increases epidermal cell adhesion and stability, resulting in hyperkeratosis and formation of scales. Previous studies have demonstrated a low serum free estriol level in the pregnant woman carrying a fetus with XLI, suggesting that serological test may be indicative of XLI . In this study, the pregnant women from two pedigrees were admitted due to high‐risk screening results in the second trimester, and the serum free estriol had a 0.121 multiple of the median in the pregnant woman from Pedigree 1 and a 0.14 multiple of the median in the pregnant woman from Pedigree 2, both of which were lower than the reference range (0.5‐2 multiples of the median).…”
Section: Discussionmentioning
confidence: 71%
“…This disorder predominantly occurs in the preauricular area, neck, axillae, anterior abdomen, and extension zone of the limbs . It is estimated that the incidence of this rare disease is 1/1500‐1/6000 . Steroid sulfatase ( STS ) gene, which is located at chromosome Xp22.31, has been proved to be a pathogenic gene of XLI.…”
Section: Introductionmentioning
confidence: 99%